STUDIES ON ULTRASTRUCTURAL IDENTIFICATION AND DISTRIBUTION OF PROTEIN-POLYSACCHARIDE IN CARTILAGE MATRIX - Matukas, Victor J. (The Rockefeller University Press, 1967)
Previous reports on the ultrastructure of cartilage matrix have described fibers, amorphous ground substance and, in some instances, dense matrix granules. The fibers are presumably collagen, but the nature of the granules is unknown. The primary purpose of this study has been to investigate the ultrastructure of cartilage matrix ih chick embryos with particular emphasis on the distribution and composition of these granules. In matrix of the zone of articular cartilage, mature collagen fibers can be seen but granules are not present. In matrix of all other zones of cartilage, fibers are smaller and granules are present. When the matrix of epiphyseal cartilage is compared to that of the zone of hypertrophic cells, fibers are similar but the granules in the latter zone are larger and more numerous. The granules in both zones were digested by hyaluronidase and positive to colloidal iron staining. Chemical analyses of cartilage from these zones indicate the hexosamine and radiosulfate content of the zone of hypertrophic cells to be higher than that of the zone of epiphyseal cartilage. The increased hexosamine was shown by column chromatography to be principally sulfated mucopolysaccharide, thereby indicating a direct correlation between size and number of granules and sulfated mucopolysaccharide content in the two zones. These data and the results of the electron microscopic histochemical studies are consistent with the concept that the granules in cartilage matrix contain acidic mucopolysaccharide.